2010
DOI: 10.2298/pac1003215n
|View full text |Cite
|
Sign up to set email alerts
|

Properties of BaTiO3 confined in nanoporous Vycor and artificial opal silica

Abstract: Using the sol-gel technique, BaTiO3 was embedded into nanoporous Vycor and artificial vitreous opal silica for the first time. About 50 vol% of the pores was filled. In case of the Vycor glass (pore diameter 4-6 nm) only amorphous phase was revealed by XRD, IR reflectivity and Raman spectra. After additional gradual annealing, no crystallization was achieved. Chemical reaction with the SiO2 skeleton started at ~1000 K. The room-temperature IR and Raman spectra clearly show characteristic vibrational modes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…As a conclusion, it was thought that the relative permittivity of 1.3 and dielectric loss of 1 © 10 ¹3 were in accordance with literature values, e.g., relative permittivity of 1.1 at 1 MHz for an aerogel with porosity of 95% prepared by Kawakami and Uehara, 4) and the relative permittivity of 1.25 and dielectric loss of 5 © 10 ¹4 at 1 kHz for an aerogel with porosity of 92% prepared by Brüesh et al 5) As shown in Fig. 9, the relative permittivity of the BaTiO 3 -silica aerogel nanocomposites increased slowly with increasing BaTiO 3 loading, reach about 2.1 for the BT/S = 20/100 sample, However, these dielectric properties were considered to be proper in comparison with a report by Nuzhnyy et al 10) They confined BaTiO 3 in a nanoporous artificial opal silica with 35 to 40 vol % porosity, where the BaTiO 3 content was 45 wt % and filled about 50 vol % of the pores. The relative permittivity and dielectric loss in this case decreased with increasing frequency to become almost constant, where the relative permittivity was 5 to 10 in the range of 10 MHz to 1 GHz.…”
Section: Dielectric Properties Of Batio 3 -Silica Aerogel Nanocomposimentioning
confidence: 54%
See 1 more Smart Citation
“…As a conclusion, it was thought that the relative permittivity of 1.3 and dielectric loss of 1 © 10 ¹3 were in accordance with literature values, e.g., relative permittivity of 1.1 at 1 MHz for an aerogel with porosity of 95% prepared by Kawakami and Uehara, 4) and the relative permittivity of 1.25 and dielectric loss of 5 © 10 ¹4 at 1 kHz for an aerogel with porosity of 92% prepared by Brüesh et al 5) As shown in Fig. 9, the relative permittivity of the BaTiO 3 -silica aerogel nanocomposites increased slowly with increasing BaTiO 3 loading, reach about 2.1 for the BT/S = 20/100 sample, However, these dielectric properties were considered to be proper in comparison with a report by Nuzhnyy et al 10) They confined BaTiO 3 in a nanoporous artificial opal silica with 35 to 40 vol % porosity, where the BaTiO 3 content was 45 wt % and filled about 50 vol % of the pores. The relative permittivity and dielectric loss in this case decreased with increasing frequency to become almost constant, where the relative permittivity was 5 to 10 in the range of 10 MHz to 1 GHz.…”
Section: Dielectric Properties Of Batio 3 -Silica Aerogel Nanocomposimentioning
confidence: 54%
“…10) In addition, there have been some reports on the enhancement of permittivity by constructing a BaTiO 3 core-silica shell nanostructure, where silica was coated on the surface of BaTiO 3 particles, and used for Malti-Layer Ceramic Capacitor, high-frequency dielectric applications, 14) and supercapacitors. 15) However, these were not porous materials.…”
Section: )13)mentioning
confidence: 99%
“…The quasi-optical THz measurements were completed with complex permittivity calculations based on the Maxwell's equations. More details and references on the used method are in [7], [18], [26], [27].…”
Section: Spectra Of Dielectric Permittivity Of Rare-earth Nanocommentioning
confidence: 99%
“…The artificial opal periodical matrices prepared by sedimentation of amorphous silica nanoballs of 200-400 nm diameter [17] have 35-40 vol% porosity with percolated pores of complex topology and sizes from zero up to ∼50 nm. The opal-based composites are prepared by impregnation of the pores with magnetic ferrites [17] or ferroelectric BaTiO 3 [18]. Owing to periodicity of the matrix and embedded nanoparticles, opal-based composites have a number of specific features.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric and ac conductivity spectra were measured using impedance methods by the techniques described in [7,8]. Standard LF dielectric measurements were performed with the dielectric analyzer Novocontrol Alpha AN, HF measurements -with the Novocontrol BDS 2100 coaxial sample cell and Agilent 4291B impedance analyzer, MW measurements - 1-4799-4580-1/14/$31.00 ©2014 IEEE with the open-end coaxial probe and Agilent E8364B vector network analyzer.…”
Section: Processing and Experimental Techniquesmentioning
confidence: 99%